Increased fire activity at the Triassic/Jurassic boundary in Greenland due to climate-driven floral change - Belcher, C; Mander, L; Rein, G; Jervis, F; Haworth, M; Hesselbo, S; Glasspool, I; McElwain, J (2010)
One of the largest mass extinctions of the past 600 million years (Myr) occurred 200 Myr ago, at the Triassic/Jurassic boundary. The major floral and faunal turnovers have been linked to a marked increase in atmospheric carbon dioxide levels, probably resulting from massive volcanism in the Central Atlantic Magmatic Province. Future climate change predictions suggest that fire activity may increase, in part because higher global temperatures are thought to increase storminess. Here we use palaeontological reconstructions of the fossil flora from East Greenland to assess forest flammability along with records of fossil charcoal preserved in the rocks to show that fire activity increased markedly across the Triassic/Jurassic boundary. We find a fivefold increase in the abundance of fossil charcoal in the earliest Jurassic, which we attribute to a climate-driven shift from a prevalence of broad-leaved taxa to a predominantly narrow-leaved assemblage. Our fire calorimetry experiments show that narrow leaf morphologies are more flammable than broad-leaved morphologies. We suggest that the warming associated with increased atmospheric carbon dioxide levels favoured a dominance of narrow-leaved plants, which, coupled with more frequent lightening strikes, led to an increase in fire activity at the Triassic/Jurassic boundary. © 2010 Macmillan Publishers Limited. All rights reserved.